Dietary EPA Increases Rat Mortality in Diabetes Mellitus, a Phenomenon Which Is Compensated by Green Tea Extract - Thibault Leger; Beibei He; Kasra Azarnoush; Chrystèle Jouve; Jean-Paul Rigaudiere; Florent Joffre; Damien Bouvier; Vincent Sapin; Bruno Pereira; Luc Demaison (MDPI AG, 2019)
Diabetes is characterized by a high mortality rate which is often associated with heart failure. Green tea and eicosapentaenoic acid (EPA) are known to lessen some of the harmful impacts of diabetes and to exert cardio-protection. The aim of the study was to determine the effects of EPA, green tea extract (GTE), and a combination of both on the cardiac consequences of diabetes mellitus, induced in Wistar rats by injection of a low dose of streptozotocin (33 mg/kg) combined with a high fat diet. Cardiac mechanical function, coronary reactivity, and parameters of oxidative stress, inflammation, and energy metabolism were evaluated. In the context of diabetes, GTE alone limited several diabetes-related symptoms such as inflammation. It also slightly improved coronary reactivity and considerably enhanced lipid metabolism. EPA alone caused the rapid death of the animals, but this effect was negated by the addition of GTE in the diet. EPA and GTE combined enhanced coronary reactivity considerably more than GTE alone. In a context of significant oxidative stress such as during diabetes mellitus, EPA enrichment constitutes a risk factor for animal survival. It is essential to associate it with the antioxidants contained in GTE in order to decrease mortality rate and preserve cardiac function.